2016
DOI: 10.1155/2016/6178575
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired Visual Motor Coordination in Obese Adults

Abstract: Objective. To investigate whether obesity alters the sensory motor integration process and movement outcome during a visual rhythmic coordination task. Methods. 88 participants (44 obese and 44 matched control) sat on a chair equipped with a wrist pendulum oscillating in the sagittal plane. The task was to swing the pendulum in synchrony with a moving visual stimulus displayed on a screen. Results. Obese participants demonstrated significantly (p < 0.01) higher values for continuous relative phase (CRP) indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…As such, difficulties in the preservation of the speed and accuracy balance affect the interaction between individuals and the environment around them. The presence of group differences for obese participants in the quality of movement adds further evidence to the hypothesis that obese disrupts the typical sensory integration process (D'Hondt et al 2011;Gaul et al 2016). As participation in physical activity often relies on the ability to coordinate movements quickly and accurately albeit, on a whole body level, problems in this process can result in difficulties participating in such activities.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…As such, difficulties in the preservation of the speed and accuracy balance affect the interaction between individuals and the environment around them. The presence of group differences for obese participants in the quality of movement adds further evidence to the hypothesis that obese disrupts the typical sensory integration process (D'Hondt et al 2011;Gaul et al 2016). As participation in physical activity often relies on the ability to coordinate movements quickly and accurately albeit, on a whole body level, problems in this process can result in difficulties participating in such activities.…”
Section: Discussionmentioning
confidence: 79%
“…These studies have found differences in a variety of facets of cognitive function such as visuospatial skill, memory, sensory integration and attention, mathematical ability, and motor skill throughout the lifespan from children to elderly adults (Prickett et al 2014;Wan et al 2014;Liang et al 2014;Wang et al 2016;Scarpina et al 2016). A recent study by Gaul et al (2016) suggested that obesity affects the sensory integration process in a visual-motor coordination task. This study found that morbidly obese adults demonstrated significantly poorer performance during a visual-motor synchronisation task when compared to a healthy weight control group (Gaul et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is rare research on the visual‐motor coordination with digitalised equipment [9–12]. For example, David et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, David et al . [9] investigated whether obesity affected the visual motor coordination via a special task which required participants to swing the pendulum synchronically with a moving visual signal displayed on a screen. There was no digitalised system to monitor the participants’ performance and the conclusion was depended on the final results of the task, lacking the analysis of the details.…”
Section: Introductionmentioning
confidence: 99%